Commercial fishers say they shun child labor at sea - Mallari, Delfin T.,Jr. (2017)
A national group of commercial fishers and fish traders denied they were engaged in child labor or illegal fishing in Tayabas and Lamon bays.
Keywords: Lucena City (Quezon) -- Fishing; Child labor